Comments on the future of EU capital markets - Luigi Spaventa (EIB Papers, 1999)
The process that so many people are envisaging for EU capital markets may be summarised approximately as follows: The single currency will eliminate currency risk. This will encourage a diversification by investors based upon other risk considerations. This will lead to a tremendous growth in capital markets. In turn this will stimulate the EU economy because of the well-documented link between financial development and economic growth. While not dismissing this logic, let me advance some doubts about the speed with which this may happen. Let us start by considering supply. Are we really going to see in Europe a large increase in the number of companies seeking access to markets either making initial public offerings (IPOs) or issuing securitised debt? Here we should distinguish between cross-border offerings by companies that are already listed somewhere, and previously unlisted companies. As shown by Colin Mayer's data for 1995-97, the former category, cross-border listings by already quoted companies, has been around for some years. Indeed, it is a phenomenon that is likely to diminish exactly because of EMU and the unification of financial markets. For example, the alliance between London and Frankfurt means that there will be a de-listing of German shares in London together with a de-listing of English shares in Frankfurt. However, this has very little effect on the overall size of the combined stock markets.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Finanzmarkt; EU-Staaten